Aloe vera-loaded natural rubber latex dressing as a potential complementary treatment for psoriasis - Herculano, Rondinelli Donizetti [UNESP]; dos Santos, Thainá Oliveira [UNESP]; de Barros, Natan Roberto; Pegorin Brasil, Giovana Sant'Ana [UNESP]; Scontri, Mateus [UNESP]; Carvalho, Bruna Gregatti; Mecwan, Marvin; Farhadi, Neda; Kawakita, Satoru; Perego, Caio Humberto [UNESP]; Carvalho, Flávio Alexandre [UNESP]; dos Santos, André Gonzaga [UNESP]; et al. (Elsevier, 2023)
Psoriasis is a disease that causes keratinocytes to proliferate ten times faster than normal, resulting in chronic inflammation and immune cell infiltration in the skin. Aloe vera (A. vera) creams have been used topically for treating psoriasis because they contain several antioxidant species; however, they have several limitations. Natural rubber latex (NRL) has been used as occlusive dressings to promote wound healing by stimulating cell proliferation, neoangiogenesis, and extracellular matrix formation. In this work, we developed a new A. vera-releasing NRL dressing by a solvent casting method to load A. vera into NRL. FTIR and rheological analyzes revealed no covalent interactions between A. vera and NRL in the dressing. We observed that 58.8 % of the loaded A. vera, present on the surface and inside the dressing, was released after 4 days. Biocompatibility and hemocompatibility were validated in vitro using human dermal fibroblasts and sheep blood, respectively. We observed that ~70 % of the free antioxidant properties of A. vera were preserved, and the total phenolic content was 2.31-fold higher than NRL alone. In summary, we combined the antipsoriatic properties of A. vera with the healing activity of NRL to generate a novel occlusive dressing that may be indicated for the management and/or treatment of psoriasis symptoms simply and economically.
Keywords: Aloe vera; Complementary treatment; Natural rubber latex; Occlusive dressing; Psoriasis